Atmospheric impact of 2-methylpentanal emissions: kinetics, photochemistry, and formation of secondary pollutants - M. Asensio; M. Asensio; S. Blázquez; S. Blázquez; S. Blázquez; M. Antiñolo; M. Antiñolo; J. Albaladejo; J. Albaladejo; E. Jiménez; E. Jiménez (Atmospheric Chemistry and Physics, 2023)
The tropospheric fate of 2-methylpentanal (2MP) has been investigated in this work. First, the photochemistry of 2MP under simulated solar conditions was investigated by determining the UV absorption cross sections (220–360 nm) and the effective photolysis quantum yield in the UV solar actinic region (λ > 290 nm). The photolysis rate coefficient in that region was estimated using a radiative transfer model. Photolysis products were identified by Fourier transform infrared (FTIR) spectroscopy. Secondly, a kinetic study of the chlorine (Cl) and hydroxyl (OH) reactions of 2MP was also performed at 298 K and as a function of temperature (263–353 K), respectively. For the Cl reaction, a relative kinetic method was used in a smog chamber coupled to FTIR spectroscopy, whereas for the OH reaction, the pulsed laser photolysis (PLP) with laser-induced fluorescence (LIF) technique was employed. The estimated lifetime of 2MP depends on the location, the season, and the time of the day. Under mild–strong irradiation conditions, UV photolysis of 2MP may compete with its OH reaction in a mid-latitude inland urban atmosphere, while Cl reaction dominates in mid-latitude coastal urban areas at dawn. Finally, the gaseous product distribution of the Cl and OH reactions was measured in a smog chamber as well as the formation of secondary organic aerosols (SOAs) in the Cl reaction and its size distribution (diameter between 5.6 and 560 nm). The implications for air quality are discussed based on the observed products.